Stability of planetary systems within the S-star cluster: the solar system analogues - Davari, Nazanin; Capuzzo-Dolcetta, Roberto; Spurzem, Rainer (Monthly notices of the Royal Astronomical Society, 2022)
A dynamically relaxed dense cluster comprised of about 40 stars (the so-called S-stars) inhabits the central region of our Galaxy. Their stars revolve around the Sgr A* massive object. To understand the dynamical evolution of planetary systems in a particular environment like that around Sgr A*, we carry out direct N-body simulations of planetary systems embedded in the S-star cluster. In this work, we investigate the short-term stability of the planets orbiting around S-stars after their close interactions with the central massive black hole of our Galaxy. We find that planetary systems go through encounters with the supermassive black hole (SMBH) and the nearby stars. We determine the frequency and the strength of planetary systems’ encounters with the nearby stars as these encounters remarkably increase for systems assigned to S-stars closer to the SMBH. The SMBH severely destabilizes the planetary systems, though we noted that the small oscillations in the mutual eccentricity and inclination of the planetary system could be caused by the planet-planet coupling and the near-resonance effect between the two planets. We obtain estimates of the fraction of survivor planets ($\sim 51{{\ \rm per\ cent}}$), and find that planets stripped from their hosting star are generally captured on close orbits around Sgr A*. We notify while gas giants are tidally disrupted, terrestrial planets do not. We estimate that Sgr A* flares can be due to the tidal disruption events of starless giant planets.